Non-contrast pulmonary perfusion MRI in patients with cystic fibrosis. Issue 139 (June 2021) - Kunz, A.S.; Weng, A.M.; Wech, T.; Knapp, J.; Petritsch, B.; Hebestreit, H.; Bley, T.A.; Köstler, H.; Veldhoen, S.
Highlights: Pulmonary perfusion deficits can be visualized by SENCEFUL MRI. Peak-to-Offset ratios possible objective marker for pulmonary perfusion impairment. SENCEFUL MRI does not require breath holds or contrast for functional lung imaging. SENCEFUL MRI could support monitoring chronic lung diseases like cystic fibrosis. Abstract: Purpose: This study aimed to assess the feasibility of Self-gated Non–Contrast-Enhanced Functional Lung (SENCEFUL) MRI for detection of pulmonary perfusion deficits in patients with cystic fibrosis. Methods: Twenty patients with cystic fibrosis and 20 matched healthy controls underwent SENCEFUL-MRI at 1.5 T with reconstruction of perfusion and perfusion phase maps (i.e. comparable to pulse wave delays). Four blinded readers rated both types of maps separately followed by simultaneous assessment thereof. Perfusion phase data was plotted in histograms and a Peak-to-Offset ratio was calculated for comparison to subjective scoring and correlation (Spearman) to lung function parameters. Sensitivity, specificity and positive and negative predictive values were calculated for subjective scoring and Peak-to-Offset ratios. Intraclass correlation (ICC) was used to assess the interrater agreement. Results: Readers attributed pathological ratings 2.2–3.5 times more frequently to the CF-group. The sensitivity with regard to a correct assignment to CF was similar between ratings (perfusion only vs. perfusions phase only vs. simultaneous assessment: 0.54−0.56), while specificity increased from 0.75 to 0.85 for simultaneous assessment. ICC was 0.77−0.84 for subjective scoring. ROC-analysis of Peak-to-Offset ratios on a mean per-subject basis revealed a sensitivity of 0.75 and specificity of 0.85 (PPV 0.83, NPV 0.77). Functional pulmonary parameters indicative of bronchial obstruction and Peak-to-Offset ratios showed positive correlation (FEV1: 0.77; FEF75: 0.76). Conclusions: SENCEFUL-MRI bears the potential for monitoring CF including disease-associated patterns of altered pulmonary perfusion. The proposed Peak-to-Offset ratio derived from pulmonary perfusion phase measurements could represent an objective future marker for perfusion impairment.